Plasmon–Exciton Coupling Effect on Plasmon Damping - Lulu Ye; Weidong Zhang; Aiqin Hu; Hai Lin; Jinglin Tang; Yunkun Wang; Chenxinyu Pan; Pan Wang; Xin Guo; Limin Tong; Yunan Gao; Qihuang Gong; et al. (Advanced Photonics Research, 2022)
Plasmon decay via the surface or interface is a critical process for practical energy conversion and plasmonic catalysis. However, the relationship between plasmon damping and the coupling between the plasmon and 2D materials is still unclear. The spectral splitting due to plasmon–exciton interaction impedes the conventional single‐particle method to evaluate the plasmon damping rate by spectral linewidth. The interaction between a single gold nanorod and 2D materials using the single‐particle spectroscopy technique assisted with in situ nanomanipulation is investigated. The approach allows to indisputably identify that the plasmon–exciton coupling would induce plasmon damping in the GNR–WSe2 hybrid. It is confirmed that the resonant energy transfer channel dominates the plasmon decay rather than the charge transfer channel in the GNR–graphene hybrid first. The contribution of the charge transfer channel by using thin hBN layers as an intermediate medium to block the charge transfer is excluded. It is also found that the contact layer between the GNR and 2D materials contributes most of the interfacial plasmon damping. These findings contribute to a deep understanding of interfacial excitonic effects on the plasmon and 2D materials hybrid.